VALUE CREATION THROUGH BUSINESS MODEL INNOVATION AND VERTICAL INTEGRATION: A CASE STUDY OF BINAWAN GROUP - Hasriani Hasriani; Awang Darmawan Putra; Agung Priyono (Journal of Management and Leadership, 2026)
This study analyzes Business Model Innovation (BMI) implemented by Binawan Group as a value creation strategy through an integrated business ecosystem encompassing eight clusters, namely International Recruitment Services, Education & Training, Tertiary and Secondary Healthcare, Primary and Aesthetic Healthcare, Food & Beverage, IT Infrastructure & Solution, Property, and Agriculture. Using a qualitative case study approach, the analysis is grounded in the Business Model Canvas framework, vertical integration theory, and Resource-Based Theory - VRIO. Binawan Group creates value through four mechanisms: an integrated HR supply chain, cross-subsidization across clusters, brand equity synergy, and operational efficiency through internal digital platforms. This research contributes to strategic management literature regarding BMI in health-based conglomerates within developing economies.